An expanded concept of Madisonia including miscellaneous species of Pleurothallidinae (Orchidaceae): Evidence from molecular analysis - Smidt, Eric De Camargo; Toscano De Brito, A. L.V.; Mauad, Anna Victoria Silvério R.; Morales, Nicolás Gutiérrez [UNESP] (Magnolia Press, 2021)
Prior taxonomic studies in subtribe Pleurothallidinae have suggested a close relationship between miscellaneous species featuring long-repent, segmented rhizomes, abbreviated ramicauls, few-flowered inflorescences, and flowers with partially connate sepals and trilobed lip. The lack of phylogenetic information for most species has prevented further conclusions or changes in their taxonomy; and as a result, they are currently assigned to several unrelated genera: Anathallis, Madisonia, Pabstiella, Pleurothallis, Sansonia and Specklinia. We performed phylogenetic analyses using nuclear (nrITS) and five plastid (matK, psbD-trnT, rps16-trnQ, trnH-psbA and trnS-trnG) markers and demonstrated that these species form an isolated clade which requires generic recognition. The name Madisonia, previously a monotypic genus endemic of the Amazon basin, is re-circumscribed and expanded to include nine species distributed in the Atlantic Rainforest and the Caribbean. Eight new nomenclatural combinations are proposed.
Keywords: Anathallis; Neotropics; Pabstiella; Sansonia; Specklinia; Systematics